Drooling and sialorrhoea - Diz Dios, Pedro; Limeres Posse, Jacobo (Henry Stewart Talks, 2017)
Defining sialorrhoea & drooling, Causes for drooling in children and adults, Drooling & neurological disorders, Effects of drooling, Tools for drooling assessment, Pharmacological approaches vs. surgical procedures, The creation of a “drooling team”, Individualised therapeutic strategy